Circadian genes polymorphism and breeding phenology in a resident bird, the yellow‐legged gull. (19th September 2017) - Romano, A.; Possenti, C. D.; Caprioli, M.; Gatti, E.; Gianfranceschi, L.; Rubolini, D.; Saino, N.; Parolini, M.
Abstract: In species living in seasonally variable environments, the ability to synchronize the timing of breeding with the peak of critical resources is under positive selection within populations. The temporal scheduling of animal annual cycle is controlled by endogenous rhythms, which are set by 'circadian clock' genes. Many studies have supported the hypothesis that length polymorphism in some 'phenological genes' is associated with differences in the photoperiodic responses among individuals and populations. However, evidence is inconsistent across species, genes and phenological traits. Among birds, there is a dearth of knowledge concerning the gene‐phenotype association in non‐migratory species. To contribute filling this gap, here we analyzed clutch initiation date of females of a species resident at temperate latitudes, the yellow‐legged gull ( Larus michahellis ), in relation to the length polymorphism at four loci previously associated with breeding and migration phenology in other species: Adcyap1 and Npas2 genes, as well as two regions of the Clock gene. Although polymorphism was observed at three loci, allele size of the candidate genes seems not to predict the timing of breeding in females. In addition, similar genotype frequencies of all the analyzed genes were observed in early compared to late breeding females. Our results therefore suggest that the associations between photoperiodic candidate genes and breeding phenotype are not general across species and might represent adaptations of individual populations to the local environment. Abstract : Polymorphism in some 'phenological genes' has been shown to predict phenology in some migratory birds, but there is a dearth of knowledge for non‐migratory species. Despite detecting high polymorphism, we did not find any significant association between photoperiodic candidate genes and breeding phenotype in a species resident at temperate latitudes, the yellow‐legged gull. We therefore suggest that the gene‐phenotype association is not general across species and might represent adaptations of individual populations to the local environment.